Simulation of the laser cladding process using discrete particles - Pacheco, Jeferson Trevizan (2021)
Additive Manufacturing (AM) is a technology that covers different manufacturing processes from the addition of materials. For processes that use the raw material in the form of metallic powder, describe the thermal, mechanical and metallurgical behavior of the particles is hard. The use of numerical simulation is an alternative to describe the complex physical behavior underlying of theses processes, as well as to predict defects and geometric shapes. In this context, this work aims to simulate the thermal interaction between spherical particles and a laser source, the associated changes in mechanical properties and an accurate contact model of particle to particle and particle to rigid obstacles. The Hertz-Mindlin+JKR contact model with aggregationis used to account for both repulsive and attractive forces, to properly simulate particle bouncing and/or clustering particle. It is observed that the variation of some parameters in the simulation of the laser cladding process influences the behavior of the particles. Analyzing two particles, it is observed that the temperature variation affects the mechanical behavior after the contact between particles and between particles and rigid obstacles. It can be noticed that the increase in the laser power results in an increase in the particles temperature, while an increase in the initial velocity of the particles results in less heating. In relation to cluster of particles, it can be noticed that the increase in surface energy results in more particles together, while the increase in laser power results in only an increase in temperature. Regarding the initial velocity of the particles, it is observed that increasing this parameter results in fewer cluster of particles.